„Między harmonią a chaosem” : Obrazy przyrody w wierszach Anny Frajlich jako język diagnozowania świata .......... 275 - Jakubowska-Ożóg, Alicja (Tu jestem / zamieszkuję własne życie : studia i szkice o twórczości Anny Frajlich, 2018)
“BETWEEN HARMONY AND CHAOS”: THE IMAGE OF NATURE IN ANNA FRAJLICH’S POEMS AS THE LANGUAGE OF DIAGNOSING THE WORLDThis article discusses the presence in Anna Frajlich's poems of characteristic motifs illustrating both harmony and chaos in the world. It refers primarily to the texts in which the poet perceives images that can be characterised as beautiful, describing the search and desire for beauty or recording beauty, but it also evokes images which contradict order both in the external and spiritual spheres of the central figure of the confessions.